2021
DOI: 10.3390/su13158336
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Agricultural Trade on Economic Growth and Environmental Pollution: Evidence from Bangladesh Using ARDL in the Presence of Structural Breaks

Abstract: Agricultural trade significantly promotes the economic boom in developing countries. Extensive traditional agricultural production methods have increased the pressure on the agricultural environment by expanding agricultural trade, which has attracted the attention of many scholars. This study aims to empirically examine the impacts of agricultural trade on economic growth and agricultural environmental pollution in Bangladesh from 1972 to 2019, using an Auto Regressive Distributed Lag (ARDL) model with a stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…In both cases, the study variables were observed to be stationary at the first difference after logarithmic transformation, which was concurred to the findings of Ghimire et al. [ 82 ].…”
Section: Resultssupporting
confidence: 91%
“…In both cases, the study variables were observed to be stationary at the first difference after logarithmic transformation, which was concurred to the findings of Ghimire et al. [ 82 ].…”
Section: Resultssupporting
confidence: 91%
“…For example, when the value of capital productivity is small, the degree of environmental pollution will gradually deepen under the influence of excessive energy consumption and high capital waste. After leveling the capital variable (unit hundred million yuan) and the nominal GDP variable (unit hundred million yuan), respectively, and after effectively removing the price factor, real capital (RK i ) and real output (RGDP i ) can be obtained [ 14 ]. The variable of capital productivity can be expressed by the ratio generated by these two items, and it can also be used as the expression method of technical effect, which is cp i .…”
Section: Methodsmentioning
confidence: 99%
“…Business practices need to preserve the environment for green and corporate social responsibilities to be successful. According to numerous studies (Ghimire et al, 2021; Huang et al, 2021; Nguyen et al, 2021; Xu et al, 2020; Yang et al, 2020), environmental responsibility of managers is the most important factor in environmental behavior. Businesses are influenced to go green by top management and stakeholders (Bakos et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, the economic development pattern promotes the consumption of energy resources, the emission of greenhouse gases, and pollution. For temporary economic growth, carbon development will never harm the environment (Ghimire et al, 2021). For Bangladesh to foster robust economic development, however, the relationship between economic development and environmental protection should be addressed properly and the concept that protecting the ecological environment is essential to fostering productivity must be firmly established.…”
mentioning
confidence: 99%